Enhancing water productivity and crop yield through participatory approaches in small-scale irrigation schemes: A case study of shimburit small scale irrigation schemes in the Amhara region, Ethiopia - Tewabe, Dires (International Journal on Food, Agriculture and Natural Resources, 2025)
Small-scale irrigation schemes in Ethiopia are pivotal for improving agricultural productivity and food security. However, challenges such as poor management, infrastructural deficiencies, and suboptimal agronomic practices hinder their potential. This study evaluates the Shimburit small-scale irrigation scheme in Ethiopia’s Amhara region, focusing on water productivity and the impact of improved irrigation technologies. Employing a mixed-method approach, data were collected through surveys, interviews, and field demonstrations comparing full-package treatments (integrated advanced irrigation and crop management) with conventional farmer practices. Three representative locations were selected from local farmers as a replications and wheat was used as a test crop to demonstrate improved water and crop technologies in this scheme. The results revealed significant challenges in the sustainability of the schemes, with current irrigated areas reduced to 25% of the initially designed capacity. Poor water management practices, seepage in unlined canals, and inadequate maintenance were identified as major issues. However, the adoption of improved irrigation technologies demonstrated substantial benefits. The result showed that the full-package treatment gave 3.97 tons ha-1 of wheat yield (significantly outperformed conventional farmer practices (2.47 tons ha-1), with water productivity increasing from 0.55 to 0.94 kg m-3. The result reveals that adopting the advanced irrigation and crop management practice improve wheat yield by 60.7% and water productivity by 70.9% as compared to the farmer’s conventional practice. The study revealed that adopting improved technologies, rehabilitating infrastructure, and building farmer capacity are essential for enhancing irrigation performance and supporting Ethiopia’s agricultural development goals.Keywords: Wheat, Improved Practices, Conventional Practice, Water Productivity